Climate change in the Ak-Shiyrak massive area and its impact on glaciers - Yu. A. Podrezova; I. A. Pavlova (Лëд и снег, 2017)
The data from Tien Shan meteorological station (3614  m  a.s.l.) were used to analyze the climate changes (the air temperature and precipitation) in the area of glaciation of the Ak-Shyirak massive over the period of 1930–2015 years. In 1999, this station had been moved to a new position, and for the later years, data on the air temperature and precipitation were brought to homogeneous series by methods of differences and correlations. Coefficients of linear trends of annual/monthly values of temperatures and precipitation sums were calculated for the following three periods: 1930–1975 – stable global climate (b1); 1976–2015 – global warming  (b2), and 1930–2015  – period of instrumental observations as a whole  (b3). In addition, for the practical use, we calculated climatic values of the temperature and precipitation for different standard time intervals within the period under investigation. It was revealed that the average annual temperatures in the region rose over the years at the rate of 0,188 °C/10 years, while in 1930–1975 years this rate was 3,5 times smaller (b1 = 0,110 °C/10 years) than in 1976–2015 years (b2 = 0,375 °C/10 years). The highest rates were recorded in February (b2 = 1,043 °C/10 years) and March (b2 = 0,855 °C/10 years). Precipitations are known to have significant inter-annual variability (especially in 1975–2000), so only the b3 trend is used as the rep‑ resentative one, obtained over the whole period of observations. During this period, the annual sum of pre‑ cipitation decreased at the rate of −7,88 mm/10 years, but during the seasons both, decreasing and increas‑ ing in precipitation, was observed within limits of changes of the trends: from −4,420 mm/10 years (July) to 0,743 mm/10 years (February). These climate changes were compared with decrease of the glaciation param‑ eters in the Ak-Shyirak massive for 1943–1976 and 1977–2003 periods, in particular, area (ΔS), height of the glacier surfaces (ΔH), and their volumes (ΔV). By the second period, the rate of decreasing of these param‑ eters had grown by the factor 1.5–2, while the temperature changes according to the above trends increased, on the average for a year, by factor 2.7, and the change in precipitation decreased by 20%.